Learning The Indonesian Language And Culture as A Gateway to Intercultural Communication : Belajar Bahasa dan Budaya Indonesia Sebagai Pintu Gerbang Komunikasi Antarbudaya - Turistiati, Ade Tuti; Ray Djayalaras Putra, Kevin; Sofwan Jauhari, Akhmad; Faikar Agung Ramadhan, Hafizh (Universitas Lancang Kuning, 2025)
This community service implements the Memorandum of Understanding between Amikom Purwokerto University and Huachiew Chalermprakiet University (HCU), Thailand. This community service initiative emphasises the importance of learning the Indonesian culture and language. This topic is important because HCU English study program students interact and communicate with students from other countries, including Indonesia. The training materials cover Indonesian culture, including knowledge of Indonesian traditions, customs, habits, traditional cuisine, traditional clothing, and the Indonesian language. In addition, this training also explains the position and role of English in Indonesia. During the training, participants learn and practice simple Indonesian language to communicate lightly with Indonesians in person and via social media. After completing the training, based on the evaluation provided via Google Forms, participants gain more knowledge and understanding of Indonesian culture and language.